1995
DOI: 10.1111/j.1439-0450.1995.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage on the Prevalent Alum‐precipitated Haemorrhagic Septicaemia Vaccine in Pakistan and Preparation of a More Efficient Oil Adjuvant Vaccine using Dense Culture of Pasteurella multocida Roberts Type 1 on an Improved Culture Medium

Abstract: Summary Significantly drastic effects of storage on the potency of the alum‐precipitated haemorrhagic septicaemia (APHS) vaccine are reported. The APHS vaccine, studied through challenge infection of vaccinated rabbits (post‐60 days of vaccination), showed 100% potency when stored at 4 °C for 30 days. The potency dropped to 20% when storage period was extended to 60 or more days. At 30 °C, the potency reduced by 40, 40 and 60%, respectively, after 30, 60 and 90 days of storage, while, at 37 °C, the decrease wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For the majority of vaccines, especially those used in cattle, sheep and pigs, the recommended storage temperature (RST) is between 2 °C and 8 °C [ 4 ]. Vaccines stored at different temperatures could result in potency loss and impaired efficacy [ 5 – 7 ]. Furthermore, emphasis is being increased nowadays on vaccine management to protect vaccines from freezing [ 8 , 9 ] as cold chain practices tend to prioritize protecting vaccine from heat damage.…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of vaccines, especially those used in cattle, sheep and pigs, the recommended storage temperature (RST) is between 2 °C and 8 °C [ 4 ]. Vaccines stored at different temperatures could result in potency loss and impaired efficacy [ 5 – 7 ]. Furthermore, emphasis is being increased nowadays on vaccine management to protect vaccines from freezing [ 8 , 9 ] as cold chain practices tend to prioritize protecting vaccine from heat damage.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure efficacy, veterinary medicines should be protected from temperature changes, direct sunlight and moisture variations. Vaccines need to be stored at 2-8 o C (Sheikh et al, 1995;VMD, 2015) or following the manufacturer's recommendations as indicated on the medicine label (VMD, 2014). Inappropriate handling, storage and use of vaccines may result in limited, no effect or even adverse effects on human and animal health (CDC, 2015).…”
Section: Introductionmentioning
confidence: 99%